EFEKTIFITAS TARIAN UNTUK MENINGKATKAN KONSEP ORIENTASI RUANG BAGI ANAK TUNAGRAHITA RINGAN - Yana Kurniati; Amsyaruddin Amsyaruddin; Fatmawati Fatmawati (Universitas Negeri Padang, 2013)
Abstract The study is motivated to problems in the field, that in the special school children Ampek Nagari encountered mild mental retardation X class C / II had difficulty in the concept of spatial orientation. From the observation, the son of the difficulty in understanding the concept of spatial orientation right-left and front-rear. This study aims to improve the concept of spatial orientation for children with mild mental retardation shell dance. Shell dance is a dance that has distinctive features that use coconut shells. The methodology in this study are single-subject research (SSR) using ABA design. the design of a study comparing the ability of the concept of spatial orientation in young mild mental retardation X at Baseline condition, tretment conditions, and conditions of the Baseline II after given interval of time without using shell dance. Data analysis techniques are used based on the observation data in the form of Visual Analisyis Of Charts The results were analyzed included the number of observations in the baseline condition I seven times, seven times tretment condition and baseline condition II five times. The results of this study aimed at the analysis of the data in the conditions and data analysis between conditions indicating a change in the concept of spatial orientation abilities in children X into a better direction. From the results of this data acquisition can be concluded that the shell dance can be used to improve spatial orientation concepts for mild mental retardation children class C / II in SLB Ampek Nagari. Kata kunci : Tunagrahita ringan; Konsep orientasi ruang; tarian.